Therapeutic Outcomes of Patients with Multifocal Papillary Thyroid Microcarcinomas and Larger Tumors - Soh-Ching Ng; Sheng-Fong Kuo; Szu-Tah Chen; Chuen Hsueh; Bie-Yu Huang; Jen-Der Lin (International Journal of Endocrinology)
A retrospective review of 626 patients with multifocal papillary thyroid carcinoma (PTC) including 147 patients (23.5%) with multifocal papillary thyroid microcarcinoma (PTMC) from a total of 2,536 patients with PTC who visited the Chang Gung Medical Center in Linkou, Taiwan, was performed. A comparison of the clinical features between 626 multifocal and 1,910 solitary PTC cases showed that patients in the multifocal PTC group were older and had a smaller mean tumor size, a more advanced tumor-node-metastasis (TNM) stage, and a higher percentage of nonremission status compared to patients in the solitary PTC group. Of the 626 patients with multifocal PTC, the group with larger tumors showed a more advanced TNM stage, a higher percentage of lymph node metastasis and soft tissue invasion, and a higher nonremission rate compared to the multifocal PTMC group. Of the 626 patients with multifocal PTC, 25 patients (4%) died during a mean follow-up period of 7.1 ± 5.3 years. Kaplan-Meier survival curves showed a significantly lower survival rate associated with multifocal PTMC compared to that with solitary PTMC.